New tourist needs and perceptions on sustainability during the pandemic: An analysis of Paracas National Reserve, Peru - Marjorie Riofrio-Carbajal; Heber Luis Olavarria-Benavides; Daniel Amadeo Robles-Fabian; Franklin Cordova-Buiza (Innovative Marketing)
Tourism has shown relevance worldwide due to its economic and social significance. However, the pandemic has given rise to new perspectives on sustainable development. Thus, it is vital to identify new tourist needs and impressions about tourist attractions. The Paracas National Reserve attracts thousands of people yearly and seeks to protect the marine-coastal ecosystems home to extraordinary biological diversity. The study aims to define the perception of sustainability and the emerging needs of tourists from Lima, the capital of Peru, when visiting the Paracas National Reserve during the pandemic. The paper is non-experimental, quantitative, explanatory, and transversal research. A survey was applied to 83 respondents from Lima who had visited the Paracas National Reserve before and during the pandemic. For data collection, the survey technique with Google Forms was used; quantitative data were analyzed using MS Excel. The findings show that 88% of tourists prefer to travel with family or friends, 88.24% consider it essential to reduce the number of groups, 69.41% value social distancing, 60.2% note that the Reserve is well attended, 75.9% are satisfied with the activities carried out, and 94% find it a professional and entertaining experience. It is concluded that tourists from Lima are aware of valuing the biodiversity of the Paracas National Reserve during the pandemic and care for its environment. In addition, they care about staying healthy, considering all the recommended protocols.